A case of mixed tumor formed by metastasis of urothelial carcinoma and malignant lymphoma to the same lymph nodes. Issue 5 (21st June 2021) - Kobayashi, Shu; Fukuhara, Hideo; Yamamoto, Shnikuro; Karashima, Takashi; Iguchi, Mitsuko; Murakami, Ichiro; Inoue, Keiji
Abstract : Introduction: Mixed tumor in the same lymph nodes is extremely rare and no previous reports have described mixed tumor comprising urothelial carcinoma and malignant lymphoma. Case presentation: A 71‐year‐old woman visited a local clinic with a main complaint of hematuria. Imaging revealed right hydronephrosis and a mid‐ureter tumor shadow. Positron emission tomography–computed tomography showed high uptake of fluorodeoxyglucose in para‐aortic lymph nodes. Abdominal para‐aortic lymph node biopsy was performed. Pathology showed urothelial carcinoma and malignant lymphoma in the same lymph nodes, where a mixed tumor was diagnosed. Conclusion: We encountered a case of mixed tumor of urothelial carcinoma and Hodgkin lymphoma, which metastasized to the same tissues.